EDUKASI PERMAINAN JAMURAN DALAM STIMULASI PERKEMBANGAN EMOSIONAL ANAK USIA DINI - Yazida Ichsan; Fifin Al Fionita; Dwi Iriyanta Prihartana; hoerotunnisa (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2021)
In realizing the development of abilities in children, an effort is needed to meet their success. Success must be due to a plan or strategy, where this will not be far from the educational program that runs the learning process. Especially in early childhood who are still happy with playing, knowledge and insight need to build to go to the next level. This results in the development of children needing a fun learning model and using a play system. From this, this article will discuss the education of mushroom games in the development of emotional stimulants for early childhood to be a stimulant device in the emotional development of early childhood. Where in collecting data the researchers used the research method of the literature study method, which in the end the various literature studies were analyzed and concluded by the purpose of writing this article.